Ethanol Regulates Presynaptic Activity and Sedation through Presynaptic Unc13 Proteins in Drosophila. - Xu, S.; Pany, S.; Benny, K.; Tarique, K.; Al-Hatem, O.; Gajewski, K.; Leasure, J.L.; Das, J.; Roman, G. (eNeuro, 2018)
Ethanol has robust effects on presynaptic activity in many neurons, however, it is not yet clear how this drug acts within this compartment to change neural activity, nor the significance of this change on behavior and physiology in vivo. One possible presynaptic effector for ethanol is the Munc13-1 protein. Herein, we show that ethanol binding to the rat Munc13-1 C1 domain, at concentrations consistent with binge exposure, reduces diacylglycerol (DAG) binding. The inhibition of DAG binding is predicted to reduce the activity of Munc13-1 and presynaptic release. In Drosophila, we show that sedating concentrations of ethanol significantly reduce synaptic vesicle release in olfactory sensory neurons (OSNs), while having no significant impact on membrane depolarization and Ca2+ influx into the presynaptic compartment. These data indicate that ethanol targets the active zone in reducing synaptic vesicle exocytosis. Drosophila, haploinsufficent for the Munc13-1 ortholog Dunc13, are more resistant to the effect of ethanol on presynaptic inhibition. Genetically reducing the activity of Dunc13 through mutation or expression of RNAi transgenes also leads to a significant resistance to the sedative effects of ethanol. The neuronal expression of Munc13-1 in heterozygotes for a Dunc13 loss-of-function mutation can largely rescue the ethanol sedation resistance phenotype, indicating a conservation of function between Munc13-1 and Dunc13 in ethanol sedation. Hence, reducing Dunc13 activity leads to naïve physiological and behavioral resistance to sedating concentrations of ethanol. We propose that reducing Dunc13 activity, genetically or pharmacologically by ethanol binding to the C1 domain of Munc13-1/Dunc13, promotes a homeostatic response that leads to ethanol tolerance.